Complete fatty acid analysis data of flaxseed oil using GC-FID method - Danish, Mohammed (Data Brief, 2019)
The data presented in this article were generated through the gas chromatography (GC) with a flame ionization detector (FID). The flaxseed oil was converted into fatty acid methyl ester (FAME) then used in the GC with FID and observe the retention time of different fatty acid present in the flaxseed oil. The observed retention time was compared with the standard fatty acid to confirm the specific fatty acid presence in the flaxseed oil. The part of the data is used in the article “Optimization of the process variable for biodiesel production by transesterification of flaxseed oil and produced biodiesel characterizations” Renewable Energy journal (Ahmad et al., 2019).